Cervical lateral mass screw length analysis in men versus women. Issue 4 (2nd December 2021) - Morita, Kohei; Ohashi, Hiroki; Kawamura, Daichi; Tani, Satoshi; Karagiozov, Kostadin; Murayama, Yuichi
Abstract: Posterior fixations with lateral mass screws have become popular. The Roy–Camille and the Magerl techniques have been established and screw length was identified as a particularly important element. Sex and ethnicity are significant factors in cervical spine morphology, but few studies have been performed for screw length. We performed measurements using computed tomography (CT) images of adult patients hospitalized for surgery of the cervical spine, with targeted 3D data analysis. The final number of patients was 47 (33 men, 14 women) and 235 vertebrae. With the Roy–Camille technique, the screw length was longest at C3 (men: 13.0 mm ± 1.9 mm, women: 13.0 mm ± 1.9 mm) and smallest at C7 (men: 10.8 mm ± 1.8 mm, women: 9.4 mm ± 1.2 mm). With the Magerl technique, the screw length was smallest at C3 (men: 14.8 mm ± 1.6 mm, women: 14.3 mm ± 1.6 mm) and longest at C7 for men (16.8 mm ± 2.8 mm), and at C6 for women (15.4 mm ± 3.0 mm). To differ from spinal canal or pedicle, cervical lateral mass showed no obvious morphological differences from that of subjects of other ethnicity. The placement of a standard lateral mass screw would not cause complications in Japanese patients, even with the use of devices designed in North America or Europe. However, the anatomical background is essential because it is important to optimize the selection for each patient to avoid complications considering sex and individual differences.